IL-17A attracts inflammatory cells in murine lung infection with P. aeruginosa. Issue 8 (November 2016) - Wonnenberg, Bodo; Jungnickel, Christopher; Honecker, Anja; Wolf, Lisa; Voss, Meike; Bischoff, Markus; Tschernig, Thomas; Herr, Christian; Bals, Robert; Beisswenger, Christoph
IL-17A-dependent immunity is of importance in the protection against extracellular bacterial pathogens. However, IL-17A is also suggested to mediate the pathogenesis of lung diseases, such as acute respiratory distress syndrome. Here, we studied the role of IL-17A in a mouse model of acute pneumonia. IL-17A mediated the expression of keratinocyte-derived chemokine (KC) and the recruitment of inflammatory cells in mice infected with a sub-lethal dose of Pseudomonas aeruginosa . IL-17A deficiency protected mice from lethal P. aeruginosa lung infection. A sub-lethal infection with Streptococcus pneumoniae resulted in increased bacterial burden associated with increased pulmonary inflammation. Thus, the type of infectious bacteria seemed to influence the way in which IL-17A functions during pulmonary infection. Reducing pulmonary inflammation by targeting IL-17A may be a therapeutic option in acute P. aeruginosa pneumonia.